Risk Factors for Visual Impairment in an Uninsured Population and the Impact of the Affordable Care Act - Guo, Weixia (Clin Surg, 2016)
PURPOSE: To assess risk factors for visual impairment in a high-risk population of people: those without medical insurance. Secondarily, we assessed risk factors for remaining uninsured after implementation of the Affordable Care Act (ACA) and evaluated whether the ACA changed demand for local safety net ophthalmology clinic services one year after its implementation. METHODS: In a retrospective cohort study of patients who attended a community-academic partnership free ophthalmology clinic in Southeastern, Michigan between September 2012 – March 2015, we assessed the prevalence of presenting with visual impairment, the most common causes of presenting with visual impairment and used logistic regression to assess socio-demographic risk factors for visual impairment. We assessed the initial impact of the ACA on clinic utilization. We also analyzed risk factors for remaining uninsured one year after implementation of the ACA private insurance marketplace and Medicaid expansion in the state of Michigan. RESULTS: Among 335 patients, one-fifth (22%) presented with visual impairment; refractive error was the leading cause for presenting with visual impairment. Unemployment was the single significant risk factor for presenting with visual impairment after adjusting for multiple confounding factors (OR = 3.05, 95% CI 1.19–7.87, p=0.01). There was no difference in proportion of visual impairment or type of vision-threatening disease between the insured and uninsured (p=0.26). Seventy six percent of patients remained uninsured one year after ACA implementation. Patients who were white, spoke English as a first language and were US Citizens were more likely to gain insurance coverage through the ACA in our population (p≤ 0.01). There was a non-significant decline in the mean number of patient treated per clinic (52 to 43) before and after ACA implementation (p=0.69). CONCLUSION: Refractive error was a leading cause for presenting with visual impairment in this vulnerable population, and being unemployed significantly increased the risk for presenting with visual impairment. The ACA did not significantly reduce the need for our free ophthalmology services. It is critically important to continue to support safety net specialty care initiatives and policy change to provide care for those in need.